Missing persons : the impossibility of auto/biography - Evans, Mary, 1946- (Routledge, 1999)
"Auto/biography is currently one of the most popular literary genres, widely supposed to illuminate the study of the individual and his or her personal circumstances. Missing Persons suggests that auto/biography is, in fact, based on fictions, both about the person and about what it is possible to know about any one individual." "Organised into chapters which consider particular kinds of auto/biographical writing, such as work on the British Royal Family and auto/biographies of twentieth-century men, this book demonstrates the absences and evasions - indeed the 'missing persons' - of auto/biography. It will provide invaluable reading for students of women's studies, sociology and cultural studies courses."--Jacket.